Comparison of Students With and Without Problematic Smartphone Use in Light of Attachment Style - Eichenberg, Christiane; Schott, Markus; Schroiff, Athina (Frontiers in Psychiatry, 2019)
Background: Nowadays, especially media addictions are of high relevance to the psychotherapeutic practice. More recently this particularly includes excessive smartphone usage. Even though a growing number of scientific literature and also mainstream media highlights problematic smartphone use as a serious health problem there is only little research. Objective: The aim of this study was to examine this phenomenon with a focus on attachment-specific differences between students with and without problematic smartphone use. Method: A survey was carried out with all enrolled students of the Sigmund Freud University Vienna. The Smartphone Addiction Scale (SPAS) was used to differentiate between students with and without problematic smartphone use. The attachment style was assessed using the Bielefeld Questionnaire on Partnership Expectations (BFPE). Results: Of the total sample 75 of the students (15.1%) could be showed a problematic smartphone use. A positive correlation between excessive smartphone usage and an insecure attachment style was found. Discussion: Therapy for problematic smartphone use should be carried out in light of patient’s attachment style. Further research into other factors of mental stress and personality is needed to better understand problematic smartphone use.